Hollow carbon nanospheres: syntheses and applications for post lithium-ion batteries. (7th July 2020) - Luo, Jin-Min; Sun, Yong-Gang; Guo, Si-Jie; Xu, Yan-Song; Chang, Bao-Bao; Liu, Chun-Tai; Cao, An-Min; Wan, Li-Jun
Abstract : We summarized the recent progress in the synthesis approaches and representative applications of hollow carbon nanospheres, especially focused on the shape control mechanism and the unique capability as anode materials of post LIBs technologies. Abstract : Hollow carbon nanospheres (HCNs) have found broad applications in different kinds of electrochemical storage devices. The characteristic hollow structure can endow carbon electrode materials with good reaction kinetics, high mechanical reliance against structural deformation, and powerful capability toward loading functional materials, which makes them particularly interesting for different energy storage systems. In this review, we summarize the recent progresses made in the research of HCNs, focusing on the synthesis strategies and corresponding applications as high-performance electrode materials in post lithium-ion battery (LIB) systems. Besides the widely implemented template-based routes, self-template routes based on the chemical design of polymeric precursors are also introduced. Efforts directed toward the shape evolution mechanism during synthesis, as well as the control capability of different methodologies on the key structural features of HCNs (such as shape, compositions, and architectures), will also be highlighted. Furthermore, we introduce the representative applications of the prepared HCNs in post LIBs, such as lithium–sulfur batteries, sodium-ion batteries, and potassium-ion batteries. We attempt to correlate the battery performance with the structural characteristics of HCNs so as to not only make good use of the advantage of shape control, but also facilitate understanding regarding the charge storage mechanism in the newly emerging technologies.